Hubungan Pendidikan dan Pengetahuan Ibu dengan Perilaku Praktik Keluarga Mandiri Sadar Gizi pada Keluarga Bayi Usia 7-12 Bulan di Tandang Tembalang Semarang - Paramudita, Ginta; Pertiwi, Estuasih Dyah (Poltekkes Kemenkes Semarang, 2013)
In food and nutrient national action plan 2001-2005, Laws no. 25 (2000) about national development program and Indonesia sehat 2010 that 80% of family become conscious nutrient defind kadarzi is a family that have balance nutrient behavior, capable to recognize and solve the nutrient problem between each member. In 2008, kadarzi area in jawa tengah is 35,26%, semarang area 65,77%. And then kadarzi in Tembalang sub district is 61,09%.The objective of this research is t find out relation between education, knowledge with conscious nutrient of independent family practice behavior to baby within 7-12 age month in Tandang Tembalang, Semarang. This research include of explonative research which has a goal to explaining relation between education level and mother knowledge with kadarzi practice behavior. Research plan include of Crossectional research, conducted in Tandang Tembalang, Semarang. As mother population which have baby 7-12 agemonth as much as 164. Whereas, mount of sample is 128, took randomly with proportional random sampling.The Research result shown respondents which have high school level is 43%, knowledge level is 85,9% (Good), and while conscious nutrient family is 3,1%.The result of fisher exact statistic shown, there is no relation between mother education with kadarzi practice behavior p=0,126 and have no relation between mother knowledge with kadarzi practice behavior p=0,459. Suggested to policy maker for increasing promotion health so society in nutrient field, especially kadarzi indicator which has lowest achievement result is exclusive ASI feeding.